Respostas

A melhor resposta!
2014-06-14T20:27:48-03:00
3x - 2y = 1
2x + 5y = 12

3x = 1 + 2y
x = 1 + 2y
         3

Aplicando o método de substituição fica:
2 (1 + 2y) + 5y = 12
       3
2 + 4y + 5y = 12
   3
mmc (1, 3) = 3
2 + 4y + 15y = 36
4y + 15y = 36 - 2
19y = 34
y = 34/19

x = 1 + 2 (34/19)
             3
x = 1 + 68/19
           3
x = (1 + 68) : 3
             19
mmc (1, 19) = 19
x = (19 + 68) : 3
          19
x = 87 : 3
      19
x = 87 * 1
      19   3
x = 87
      57

Resposta: {87/57; 34/19}
1 5 1